Discovery of a Novel Class of Boron-Based Antibacterials with Activity against Gram-Negative Bacteria - Hernandez, Vincent (American Society for Microbiology, 2013)
Gram-negative bacteria cause approximately 70% of the infections in intensive care units. A growing number of bacterial isolates responsible for these infections are resistant to currently available antibiotics and to many in development. Most agents under development are modifications of existing drug classes, which only partially overcome existing resistance mechanisms. Therefore, new classes of Gram-negative antibacterials with truly novel modes of action are needed to circumvent these existing resistance mechanisms. We have previously identified a new a way to inhibit an aminoacyl-tRNA synthetase, leucyl-tRNA synthetase (LeuRS), in fungi via the oxaborole tRNA trapping (OBORT) mechanism. Herein, we show how we have modified the OBORT mechanism using a structure-guided approach to develop a new boron-based antibiotic class, the aminomethylbenzoxaboroles, which inhibit bacterial leucyl-tRNA synthetase and have activity against Gram-negative bacteria by largely evading the main efflux mechanisms in Escherichia coli and Pseudomonas aeruginosa. The lead analogue, AN3365, is active against Gram-negative bacteria, including Enterobacteriaceae bearing NDM-1 and KPC carbapenemases, as well as P. aeruginosa. This novel boron-based antibacterial, AN3365, has good mouse pharmacokinetics and was efficacious against E. coli and P. aeruginosa in murine thigh infection models, which suggest that this novel class of antibacterials has the potential to address this unmet medical need.